PPARβ/δ Agonism with GW501516 Increases Myotube PGC-1α Content and Reduces BCAA Media Content Independent of Changes in BCAA Catabolic Enzyme Expression - Caroline N. Rivera; Jason S. Hinkle; Rachel M. Watne; Trent C. Macgowan; Andrew J. Wommack; Roger A. Vaughan (PPAR Research)
Background. Type 2 diabetes is characterized by reduced insulin sensitivity, elevated blood metabolites, and reduced mitochondrial metabolism with reduced expression of genes governing metabolism such as peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α). PGC-1α regulates the expression of branched-chain amino acid (BCAA) metabolism, and thus, increased circulating BCAA in diabetics may be partially explained by reduced PGC-1α expression. PGC-1α functions in-part through interactions with peroxisome proliferator-activated receptor β/δ (PPARβ/δ). The present report examined the effects of the PPARβ/δ agonism on cell metabolism and related gene/protein expression of cultured myotubes, with a primary emphasis on determining the effects of GW on BCAA disposal and catabolic enzyme expression. Methods. C2C12 myotubes were treated with GW501516 (GW) for up to 24 hours. Mitochondrial and glycolytic metabolism were measured via oxygen consumption and extracellular acidification rate, respectively. Metabolic gene and protein expression were assessed via quantitative real-time polymerase chain reaction (qRT-PCR) and western blot, respectively. Media BCAA content was assessed via liquid chromatography–mass spectrometry (LC/MS). Results. GW significantly increased PGC-1α protein expression, mitochondrial content, and mitochondrial function. GW also significantly reduced BCAA content within culture media following 24-hour treatment; however, expression of BCAA catabolic enzymes/transporter was unchanged. Conclusion. These data confirm the ability of GW to increase muscle PGC-1α content and decrease BCAA media content without affecting BCAA catabolic enzymes/transporter. These findings suggest heightened BCAA uptake (and possibly metabolism) may occur without substantial changes in the protein levels of related cell machinery.